THEORETICAL CONSTRUCT AND DEVELOPMENT OF WASATIYAH MEASUREMENT INSTRUMENTS - Waston Waston; Achmad Rasyid Ridha; Kumaidi Kumaidi (Universitas Muhammadiyah Surakarta, 2023)
This study aims to produce wasatiyah (religious moderation) measurement instruments that are valid, reliable, and meet the criteria for the goodness of fit statistics based on theoretical constructs to formulate dimensions, aspects, and indicators. Wasatiyah is measured by 4 (four) dimensions, including the nationality dimension, Islamic dimension, tolerance dimension, and anti-violence dimension. Each dimension consists of 2 (two) aspects, thus there are 8 (eight) aspects and a total of 25 (twenty-five) indicators. The research subjects were 286 (two hundred and eighty-six) people for instrument 1 and 250 (two hundred and fifty) people for instrument 2. They were educators and education staff of Islamic integrated schools that are members of the Indonesian Islamic Integrated School Network (Jaringan Sekolah Islam Terpadu, JSIT). This research uses mixed methods, namely qualitative methods with a literature study approach and quantitative methods through field trials with measurement methods. In its analysis, the research used LISREL 8.8 application through reflective construction based on confirmatory factor analysis (CFA). Based on the confirmatory factor analysis, the wasatiyah construct is valid, reliable, and fit as a model. Each dimension, aspect, and indicator can reflect and shape the wasatiyah construct both on instrument 1 and instrument 2. Therefore, the measurement model of the wasatiyah theoretical construct can be accepted according to empirical data obtained from field tests. As the Ministry of Religion's program to develop moderate Islamic understanding in the nation needs to be supported by clear measurement tools, the wasatiyah measurement instruments are expected to avoid political prejudice. Wasatiyah must be defined honestly, not based on momentary political interests. It is hoped that the wasatiyah measurement instruments can be used by any institution, especially formal educational institutions, to assess the wasatiyah level of their employees, teachers, or staff. In addition, it can also be used by other Muslim communities such as youth of mosques, hijrah communities, and so on.